Coping Stress Pada Remaja Yang Menikah Di Usia Dini - Nurdjanah, Alifah, Setia Asyanti, S.Psi., M.si, Psi (2016)
Early marriages happened in adolescents have caused them to lose one of the most important duty in their adolescents period, such as preparing for their marriage and household. Adolescents who married in early age have a new role in their life as an adult. The life of marriage person always encounter problem that may cause stress. Stress can be solved by means of coping in each individual. Coping by Lazarus in Niam (2009) is the way of individuals deal with stressful situations. The purpose of this study was to determine the problems experienced by adolescents married in early age, to find out the form of the stress experienced by them, to find out the stress coping used and determine the impact of coping itself. This study applied a qualitative method with four key informants and three supporting informants. Key informants are adolescents married in early age and they married at the age of less than sixteen years old, besides, the supporting informants are the family or relatives of the key informants. In this study, researchers used interviews and observation methods as a means of data collecting technique. The result of this study determined that the problem occurs in adolescents married in early age is divided into two: internal and external problems. The internal problems experienced by informants are such a negative emotions like feeling sad, regret, and guilty, in addition, the external problems experienced are economic problems and divorce. Due to those problems, the informant experienced some physical, psychological, intellectual and interpersonal stress. The type of coping used to solve the problems is the kinds of coping on issues such as active behavior, planning, seeking instrumental support and emotions focused coping such as seeking emotional support, acceptance, denial and religiosity. Based on those coping, three of the four informants generally used emotion focused coping to solve their problems. The impact of coping that the informant used was feeling relieved after receiving the emotional support but all informants also fell that their current problems are not done yet. Keywords: Coping, Early Marriage, Adolescents, Stress